(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Adolescence plays very crucial role in human development. During this phase rapid physical, cognitive, emotional, and social changes takes place. Thus, an adolescent undergo a number of challenges and opportunities that may impact their future well being in both positive or Persons at this age n adverse manner. Therefore, an adolescent need to be treated with utmost care. The acquisition of life skills during adolescence is very significant for holistic development and overall well-being of the individual. The current paper critically examines the association between socio-demographic variable and level of life skills in the rural belt of Anand District, Gujarat. A structured questionnaire was introduced among 383 respondents. To understand the association, chi-square analysis was carried out. In order to find the direction of relation, correlation coefficient test was used. The study reveals association between life skills with socio-demographic variables viz. gender, caste, family type, occupation and education of father and mother along with participation of respondents into various co-curricular activities